Periphytic diatoms of the Mediterranean karst spring Sa Vena (Su Gologone system, Sardinia, Italy): relationships with environmental variables and effects of an extreme flash flood. Issue 3 (3rd July 2018) - Lai, Giuseppina G.; Ector, Luc; Wetzel, Carlos E.; Sechi, Nicola; Lugliè, Antonella; Padedda, Bachisio M.
ABSTRACT: In Sardinia, Italy, karst springs are strategic water resources and potential hotspots of biodiversity; however, they are understudied, and their communities remain largely unknown. This study was conducted at Sa Vena spring (Su Gologone system) to characterize the diatom communities, to describe their relationships with environmental variables, and to evaluate the impact of an extreme flash flood. High species richness, diversity, and evenness were found both in epiphytic and epilithic assemblages. Statistical analyses showed significant differences between assemblages from the 2 substrates and in assemblages from the same substrate. Differences seem due to the stronger impact of seasonal water level variations and flash flood on macrophytes than on cobbles. Further, epilithic assemblages showed more stable behavior over time, both on an annual (higher resistence) and a multiannual (higher resilience) scale. Alkalinity ( p = 0.002) and dissolved oxygen ( p = 0.004) explained a significant amount of variance in epiphytic and epilithic assemblages, respectively, according to RDA analyses; however BOD5, negatively correlated with dissolved oxygen, can be the most probable driver of epilithic diatoms. The results suggest the importance of the proper management and preservation of this biotope, both for the high biodiversity and potential vulnerability to climate change.